Influence of the result of the games on the amount of finishes and goals performed by a female futsal club - Miranda, Bruno Luiz Galvão de (2021)
The aim of this study was to investigate the influence of the result of the games on the number of submissions and goals achieved by a women's futsal club in a championship. The study is observational, with an analytical approach and cross-sectional design. The data were recorded in seven games of a local women's championship in São Luís-MA. The statistic were made using the kolmogorov-smirnov (p<0.05) and kruskal-wallis (p<0.05) tests of the Bioestat®5.3 software. It was identified that less than 4% of submissions became goals, two types of submissions were more recorded: blocked and out. According to statistics, the result of the games has no influence (p<0.05) on the number of submissions and goals scored. Although it was possible to notice that the games with victorious results presented a greater number of submissions when compared to other results (defeat or draw).